Intensidade luminosa e crescimento de mudas de pitangueiras (Eugenia uniflora) - Stefeni, Alberto Ricardo (2018)
Native fruit tree in Brazil, the Surinam cherry belongs to the family Myrtaceae, with good adaptability, and can be found in all Brazilian biomes, producing edible fruits with excellent nutraceutical characteristics and great added value potential for the agroindustry. However, there is a need to know better the growth behavior of seedlings in the process of domestication of this species. The objective of this work was to evaluate the growth of Surinam cherry seedlings from seed and mini - cutting in conditions of light intensity. Seedlings from seed propagation (sexed), and seedlings from asexual propagation (minicuttings), both approximately two years old, were transplanted to 20-liter pots containing the mixture of red latosol, commercial substrate and sand 3: 1: 1 (v / v) ratio and later were accommodated in screens with different luminous intensities. The experimental design was a completely randomized (DIC), two-factorial scheme: 2 x 5 scheme (propagation method x shading mesh), and 2 x 5 x 12 scheme (propagation method x shading meshes x months), both with 4 replicates of 5 plants per experimental unit. Five screens were implanted (Figure 1), each one differing by the level of shading, being these, (1) full sun; (2) shading with 35% intensity, (3) 35% red photoconverter screen; (4) shading with 50% intensity and (5) shading with intensity of 80%.analyzed variables were mean temperature; relative humidity; luminous intensity and rainfall; leaf area; mass and dryness of the aerial part; number of new leaves; number of shoots sown; shoot size; stem size; stem diameter; neck diameter; total plant size; size of the root system; total number of secondary roots; fresh and dry root mass; root system architecture A and B; volumetric density of the root system; increase in size of the area; increase in stem diameter; increase in number of primary shoots; increase in number of leaves; increased sprout growth; total chlorophyll; morphological characterization of seedling propagated by mini-cutting; and evaluation of seedling adaptation under field conditions. The data were submitted to the normality test of Lilliefors. The averages, whether or not transformed by (x + 1) were submitted to analysis of variance and Duncan's test (α = 0.05) with Sanest® computational application. For the growth of seedlings (Eugenia uniflora), propagated by mini cuttings and by seeds, the use of 50% and 35% shading meshes is recommended. Comparatively, the seedlings propagated by seeds presented better development when compared to seedlings from mini- uttings.The seedlings originated from the mini - set propagation show homogeneity regarding the morphological characters, which are similar to the morphological characteristics of the seedlings propagated by seeds, with the exception of shoots that showed plagiotropic growth. In field conditions the seedlings from both propagation methods showed excellent adaptability.